Assentados e não assentados no povoado Boa Vista, Capela/SE : sustentabilidade e pequena propriedade - Ribeiro Júnior, Antonio Eduardo Prado (2010)
Faced with the challenge of environmental sustainability of the planet, which requires, in addition to changes in the course of development, changes in the functioning of society and its various activities, it is important for this research to analyze the current situation of sugar cane in small farm settlers and not the village of Boa Vista, in the town of Capela. An activity that is linked to factors not always resulting in good outcomes, such as the subordination that small farmers suffer from the sugarcane industry where they are required to provide their small sugarcane production and the low prices that are not always reliable. The paper analyzes the effects of the constant growth of this activity and its influence on the environment and socio-economic aspect: trying to show the reality of a region Sergipe that has been marked by such activity, and which has stood out increasingly in recent years (re) configuration of the geographical area where this activity creates conflicts between environmental issues and the agrarian question. The aim is to analyze the various relationships between small farmers and settlers, not settlers. That is, to what extent the sugar cane interfere in the dynamics of relationships between small farmers, squatters, and not the settlers, and the power of cane sugar, still thinking of the similarities and differences of the relations of the settlers and not sitting in the relationship these two actors have with the environment in which they give. Small farms that once lived on subsistence agriculture are now also being influenced by this activity, whether it represents an alternative form of income for small farmers, or representing an activity which is unsustainable in the social and environmental. The various relationships presented in this study demonstrate the difficulties faced by small farmers in the villages Boa Vista, to maintain their cultures, mainly from cane sugar, while many small farmers reported some satisfaction in the results of their crops.